SPACE-2: A Missed Opportunity to Compare Carotid Endarterectomy, Carotid Stenting, and Best Medical Treatment in Patients with Asymptomatic Carotid Stenoses. Issue 6 (June 2016) - Eckstein, H.-H.; Reiff, T.; Ringleb, P.; Jansen, O.; Mansmann, U.; Hacke, W.; ,
Abstract : Background: Because of recent advances in best medical treatment (BMT), it is currently unclear whether any additional surgical or endovascular interventions confer additional benefit, in terms of preventing late ipsilateral carotid territory ischemic stroke in asymptomatic patients with significant carotid stenoses. The aim was to compare the stroke-preventive effects of BMT alone, with that of BMT in combination with carotid endarterectomy (CEA) or carotid artery stenting (CAS) in patients with high grade asymptomatic extracranial carotid artery stenosis. Methods: SPACE-2 was planned as a three-armed, randomized controlled trial (BMT alone vs. CEA plus BMT vs. CAS plus BMT, ISRCTN 78592017). However, because of slow patient recruitment, the three-arm study design was amended (July 2013) to become two parallel randomized studies (BMT alone vs. CEA plus BMT, and BMT alone vs. CAS plus BMT). Results: The change in study design did not lead to any significant increase in patient recruitment, and trial recruitment ceased after recruiting 513 patients over a 5 year period (CEA vs. BMT ( n  = 203); CAS vs. BMT ( n  = 197), and BMT alone ( n  = 113)). The 30 day rate of death/stroke was 1.97% for patients undergoing CEA, and 2.54% for patients undergoing CAS. No strokes or deaths occurred in the first 30 days after randomization in patients randomized to BMT. There were several potential reasons for the low recruitment rates into SPACE-2, including the ability for referring doctors to refer their patients directly for CEA or CAS outwith the trial, an inability to convince patients (who had come "mentally prepared" that an intervention was necessary) to accept BMT, and other economic constraints. Conclusions: Because of slow recruitment rates, SPACE-2 had to be stopped after randomizing only 513 patients. The German Research Foundation will provide continued funding to enable follow up of all recruited patients, and it is also planned to include these data in any future meta-analysis prepared by the Carotid Stenosis Trialists Collaboration.